Access to Railway Stations in the Netherlands - Moshe Givoni; Piet Rietveld (European Regional Science Association (ERSA), 2006)
A rail journey is rarely an end in itself but almost always part of a journey 'chain' which include access to and egress from the railway station. The integration of the rail-journey components is essential to achieving a continuous travel, door-to-door, when using the rail and to make the rail an attractive alternative to car and this requires seamless interchange at the station between the chain elements. The paper focuses on two lines of investigation with regard to the above. First, the perception of railway stations and the access journey and their importance in the perception of the railway journey is analyzed. It is assumed that the perception of the rail journey is a function of the journey generalized costs, the station perception and the quality of the access and egress journeys. Based on the data available the potential of making rail a more attractive mode by improving (through different means) the station perception is examined. The second line of investigation aims to examine how availability of car affects the use of rail and the access to station mode choice. Based on the results the paper discusses the question of how rail use can be increased through facilitating the interchange between different transport modes at railway stations.
Keywords: 330